The Effect of Liquidity Ratio, Capital Structure and Activity on Company Profitability - Syahputra, Satria Arga Dita; Imronudin (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The study aims to measure the impact of liquidity ratio, capital structure and activity on profitability in financial sector companies. This study uses an associative quantitative approach with secondary data sourced from the annual reports of companies listed on the Indonesia Stock Exchange (IDX) for the 2023 period. Sampling was carried out using the purposive sampling method with certain criteria, namely the company must consistently publish financial reports during 2023, use the rupiah currency, and include values ​​for the liquidity ratio, capital structure, asset activity ratio, and profitability. Based on these criteria, 97 companies met the requirements. Multiple regression analysis is a method for measuring research hypotheses through the use of SPSS v.29 statistical software. The results of this study indicate that the company's liquidity ratio, capital structure and asset activity ratio can have an effect on the profitability of the finance sector in 2023.